(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article explains the features of preserving the names of works of art in English from the point of view of linguistic pragmatics and linguoculturology. In addition, attempts are being made to observe and explore the local linguistic cultures of science as anthroponyms and expressions, comparisons and metaphors in the object of the Karakalpak language. The burden of the nomination process depends on the semantic requirements of interpretation in linguistics. Linguo-pragmatics and linguoculturological changes in the names of works of art in English are similar, some of them concern not only the content, but also the production and research of the correct structures for obtaining information